DESCRIPTION OF KNOWLEDGE, ATTITUDE AND CHARACTERISTICS OF PREGNANT WOMEN IN THE IMPORTANCE OF CONSUMING FEED TABLETS AT PUSKESMAS SUKAWARNA - Antri Ariani; Andria Pragholapati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
The need for iron during pregnancy increases, this increase is increased to meet the needs of the fetus to grow. Obtained pregnant women with fe coverage of 35.44% in Sukawarna health center. Interview with 10 pregnant women where the condition after consuming Fe tablets is that women feel nauseous because of the nausea effects there are some pregnant women who do not take Fe tablets.This study aims to determine the description of knowledge, attitudes of pregnant women in the importance of consuming iron tablets in Puskesmas Sukawarna. The design used is descriptive research. With data obtained through questionnaire data collection from pregnant women. Data is presented in the form of frequency distribution with univariate analysis. With a population of 130 people, and a total sample of 56 people with accidental sampling technique. The results showed that almost all respondents had good knowledge and in terms of attitude showed that more than half of respondents did not support.